Development of a flexible film made of polyvinyl alcohol with chitosan based thermosensitive hydrogel - Chih-Ling Huang; Hsun-Yu Huang; Yu-Chen Lu; Chia-Jung Cheng; Tzer-Min Lee (Elsevier, 2023)
Background/purpose: A challenge that arises with periodontal regeneration surgery has been associated with the future development of periodontal regeneration membrane to prevent gingiva and fibroblasts invade the wound and allow alveolar bone successfully regenerated. Materials and methods: Chitosan (CS) has the advantages of non-toxicity, biodegradation, biocompatibility, and has been widely used in wound dressings. A flexible film was made using polyvinyl alcohol (PVA) blending CS based thermosensitive hydrogel. Results: The proposed 2% PVA/CS hydrogel has the highest swelling ratio about 720% after 60 min incubation and keeps its area after 10 min incubation for surgery suture. The elastic modulus of 0%, 1%, 2%, and 4% PVA/CS hydrogel were 7.75 ± 1.96, 0.91 ± 0.16, 0.75 ± 0.21, and 0.37 ± 0.06 MPa, respectively. The maximum strain of 2% PVA/CS hydrogel was 101.00 ± 28.03 (%). After 8 weeks biodegradation, the remain weight of 2% PVA/CS hydrogel was 71.36 ± 0.79 (%). Conclusion: In vitro cytotoxicity tests were performed and demonstrated PVA/CS hydrogel significantly improving cell proliferation. This study realized a promising flexible film for periodontal regeneration membrane that can prevent the rapid growth of fibroblasts to invade the wound and be used for periodontal regeneration surgery.